Liquid-solid fluidized bed dynamics: experimental and computational analysis - Ferreira, Victor Oliveira (2023)
The liquid-solid fluidization is a simple process intensification strategy. The method remains underexplored, in part, due to the lack of predictability. It is not trivial to assess its internal dynamics without a robust experimental setup and the predictions of its fluid dynamics behavior rely on simple correlations that do not reflect internal variances either in time or space. On the other hand, with the advance of processing power, physics-based mathematical models can now be resolved using robust numerical methods implemented on computers. The unresolved CFD-DEM (Computational Fluid Dynamics-Discrete Elements Method) coupling is especially powerful for providing a precise description of particles' individual behavior (including interactions with other solids and the fluid) while preserving a reasonable computational cost. In this thesis, experimental methods and the unresolved CFD-DEM coupling were applied to assess the liquid-solid fluidized bed dynamics. Experimental measurements of the expansion behavior of beds were obtained for a wide variety of particles. The experimental results were used to verify the precision of the Richardson-Zaki equation and a proposed alternative method based on drag correlations. The latter has shown superior accuracy for most of the tested cases. The liquid-solid fluidized bed simulations were carried out in Lethe, an open-source CFD, DEM, CFD-DEM, and multiphysics software. Lethe simulations of the pilot-scale liquid-solid fluidized beds were validated for a wide variety of regimes. Discussions on the choice of drag correlation, the robustness of the method with different mesh topologies, and the importance of the Saffman lift force for the accurate simulation of the flow structures are provided. The validated simulations were used to assess the particles' mixing by applying the nearest-neighbors method (NNM) and the mixing index introduced by Doucet. The slowest mixing component for most of the simulations was the axial. The mixing time as a function of the inlet flow rate demonstrates a plateauing behavior for looser beds (fluid fractions above 50%). Variations in the interaction properties of particles do not seem to play an important role in the quantitative mixing. Yet, for a bed of particles with very low Stokes numbers or at very high concentrated beds, increasing the sliding friction coefficient presented a negative impact on the mixing performance.